Degradation of Human α- and β-Defensins by Culture Supernatants of Porphyromonas gingivalis Strain 381 - Carlisle, M.D. (J Innate Immun, 2009)
Porphyromonas gingivalis produces proteases capable of degrading cytokines, host heme proteins and some antimicrobial peptides. In this study, we show that P. gingivalis culture supernatants fully or partially degrade human neutrophil peptide α-defensins and human β-defensins after 30 min. This observation suggests that proteases from P. gingivalis degrade defensins and this activity could abrogate defensin-related innate immune functions.